The Role of Irony in Revealing Holocaust in the Novel by Thomas Keneally “Schindler’s Ark” - Ніколенко, Ольга Миколаїівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article deals with the novel “Schindler’s Ark” written in 1982 by Australian writer Thomas Keneally (born 1935). The subject matter of the novel is the description of tragic event during the II World War such as Holocaust. In the genre of a historic novel based on the documents, the writer revealed the complicated social processes in Europe during 1930-1940 ties. Thomas Keneally described the historic events within the life of ordinary people who lived in the terrible circumstances of the totalitarian system. The irony played the main role in revealing the subject Holocaust in this novel. The fundamentals of irony in European literature could be found in the literary works by the writers of Romanticism in the XIX-th century. They explained the role of romantic irony which became a tool for criticism the negative phenomenon in society and depicting the psychology of characters. Thomas Keneally continues the traditions of romantic irony and added to it some social, psychological and philosophical meaning. The irony in the novel by Thomas Keneally “Schindler’s Ark” plays an important role in the investigation of European society in the tragic period of the XX-th century. In the novels by Thomas Keneally irony takes place on the different levels such as plot, composition, imagology, time and space, style and language. T. Keneally broadens the meaning of irony and its function in the documentary and historic novel. The irony in the novel “Schindler’s Ark” maintains some main functions: social for explaining the anti-humanistic essence of fascism, war, racial hatred, research in investigating the tragedy of Holocaust and its consequences, psychological in revealing the psychology of people of different social class, philosophical in discussing the important issues of human life in the word, axiological dealing with the values of mercy, morality, the ability to resist violence. T. Kenealy represents the different forms of irony such as the irony of the narrator, the irony of the author, the combination of controversial documentary facts, the contradiction of phenomenon and notions, the comparison of the different points of view, self-irony, irony as inner enlightenment, catharsis. In the novel “Schindler’s Ark” by T. Kenealy the author of the article analyzed the traditions of world literature such as B. Brecht within the motive of personal financial profit from the war, N. Gogol within the motive of buying and selling the dead souls. The writer represented these motives in his own way as the events took place during the real historic time, and he found the inner power in people of past century to keep their life, humanity and culture on the Earth. The irony is a unique feature of T.Keneally’s individual style and it enriched the genre of novel